The Prisoner of the Precarious Body: An Odyssey of Dalit Women in Bama’s Sangati - Dhankar, Anshul; Devendra Kumar Sharma (SARE: Southeast Asian Review of English, 2024)
The body is regarded as a fundamental text for understanding the self, as it is interpreted as both a reflection as well as the creation of the societal structure in which it exists. The female body becomes a symbol on which the conflicting ideologies and discourses of the socio-cultural milieu are engraved. At the forefront of this, lies the body of a Dalit woman, a battleground where dynamics of power collide and the struggle for dignity and autonomy unfolds. Weighed down by the overlapping mechanisms of gender, sexuality, caste, class, and community, their bodies, therefore, become political fields of containment and control. In light of this, the present paper delves into Bama Faustina’s Sangati (2005) to covertly depict the body politics of gradated patriarchy disclosing the unfettered (s)exploitation of women but simultaneously tracing a paradigm shift through facilitating means of resistance for the Dalit women.